(NrADIOBIOLOGIQ ^ELOWEKA I VIWOTNYH (B:s (Nu^EBNOE POSOBIE (B/s - (NqRMONENKO(B, (NsAMUIL pETROWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1984)
(NsPISOK LIT(B.: (NS(B. 360 - 363s
(NuKAZ(B. (NPREDM(B., (NIMEN(B.: (NS(B. 363 - 372s
Keywords: (NrADIOBIOLOGIQs